Effect of Body Mass Index on pregnancy outcomes in nulliparous women delivering singleton babies - Liston William A; Campbell Doris M; Bhattacharya Sohinee; Bhattacharya Siladitya (BMC, 2007)
Abstract Background The increasing prevalence of obesity in young women is a major public health concern. These trends have a major impact on pregnancy outcomes in these women, which have been documented by several researchers. In a population based cohort study, using routinely collected data, this paper examines the effect of increasing Body Mass Index (BMI) on pregnancy outcomes in nulliparous women delivering singleton babies. Methods This was a retrospective cohort study, based on all nulliparous women delivering singleton babies in Aberdeen between 1976 and 2005. Women were categorized into five groups - underweight (BMI < 20 Kg/m2), normal (BMI 20 - 24.9 Kg/m2) overweight (BMI 25 - 29.9 Kg/m2), obese (BMI 30 - 34.9 Kg/m2) and morbidly obese (BMI > 35 Kg/m2). Obstetric and perinatal outcomes were compared by univariate and multivariate analyses. Results In comparison with women of BMI 20 - 24.9, morbidly obese women faced the highest risk of pre-eclampsia {OR 7.2 (95% CI 4.7, 11.2)} and underweight women the lowest {OR 0.6 (95% CI 0.5, 0.7)}. Induced labour was highest in the morbidly obese {OR 1.8 (95% CI 1.3, 2.5)} and lowest in underweight women {OR 0.8 (95% CI 0.8, 0.9)}. Emergency Caesarean section rates were highest in the morbidly obese {OR 2.8 (95% CI 2.0, 3.9)}, and comparable in women with normal and low BMI. Obese women were more likely to have postpartum haemorrhage {OR 1.5 (95% CI 1.3, 1.7)} and preterm delivery (< 33 weeks) {OR 2.0 (95% CI 1.3, 2.9)}. Birthweights less than 2,500 g were more common in underweight women {OR 1.7 (95% OR 1.2, 2.0)}. The highest risk of birth weights > 4,000 g was in the morbidly obese {OR 2.1 (95% CI 1.3, 3.2)} and the lowest in underweight women {OR 0.5 (95% CI 0.4, 0.6)}. Conclusion Increasing BMI is associated with increased incidence of pre-eclampsia, gestational hypertension, macrosomia, induction of labour and caesarean delivery; while underweight women had better pregnancy outcomes than women with normal BMI.